Pengaruh Servicescape dan Kualitas Pelayanan Frontliner Terhadap Kepuasan Nasabah (Studi Kasus Pada PT. Bank Muamalat KCU Padangsidimpuan) - Lestari, Eka; Siregar, Budi Gautama (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the impact of service quality and product quality on customer satisfaction among Mabrur savings account holders at PT. Bank Mandiri Syariah KCP Panyabungan. A quantitative approach was employed, involving a sample of 97 customers selected through incidental sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS version 23. The findings indicate that service quality significantly influences customer satisfaction (t-value = 4.820 t-table = 1.661), whereas product quality does not have a significant effect (t-value = 0.604 t-table = 1.661). Additionally, both variables collectively have a significant impact on customer satisfaction (F-value = 13.273 F-table = 3.90), with a coefficient of determination (R²) of 22%.